2017
DOI: 10.1002/ags3.12020
|View full text |Cite
|
Sign up to set email alerts
|

Robotic gastrectomy for gastric cancer: Current evidence

Abstract: The robotic system has gained wide acceptance in specialties such as urological and gynecological surgery. It has also been applied in the field of upper gastrointestinal surgery. Since the first implementation of the robotic system for the treatment of gastric adenocarcinoma, the procedure has been found to be safe and feasible. Although robotic gastrectomy does not meet our expectations and yield better results than laparoscopic gastrectomy, this procedure seems to provide several advantages over laparoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 55 publications
0
17
0
1
Order By: Relevance
“…These updates could provide essential and new insights into gastric cancer treatments in practical clinical settings. However, in the present review, we could summarize only some of the major topics and had to exclude topics on less invasive surgeries such as laparoscopic and robotic gastrectomy and clinical study regarding the surgical approach based on the sentinel node concept for early gastric cancer . However, additional updates on major topics including these topics could be summarized in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…These updates could provide essential and new insights into gastric cancer treatments in practical clinical settings. However, in the present review, we could summarize only some of the major topics and had to exclude topics on less invasive surgeries such as laparoscopic and robotic gastrectomy and clinical study regarding the surgical approach based on the sentinel node concept for early gastric cancer . However, additional updates on major topics including these topics could be summarized in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Disadvantage of the robotic operations in terms of longer operating time compared to laparoscopy was documented previously. 19,20 Robotic surgery for the treatment of gastric cancer is in the beginning phase in Turkey. Role of caseload on reducing the time spend in the operating room has been well documented previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, high operating times may be related to the learning curve. A Korean study comparing their initial (first 500 cases) vs later RG experiences found a significant reduction in operative time from a mean of 229.3 minutes to 215.7 minutes ( P < .001), which is more comparable to laparoscopic procedure times 29 …”
Section: Current Evidence Supporting Mis Gastrectomymentioning
confidence: 93%